PREVALENCE OF ANTIMICROBIAL-RESISTANT ENTEROCOCCUS FAECIUM IN COMMERCIAL CATTLE: A SYSTEMATIC REVIEW AND META-ANALYSIS - BROTTO, A. L. C.; SILVA, S. V.; SILVA, R. L. S.; ANTONIAZZI, F. B.; STIEVANO, J. M.; NAKAGHI, A. C. H.; BARBERATO-FILHO, S.; SILVA, M. T.; BERGAMASCHI, C. C. (Ars Veterinaria, 2022)
The use of antimicrobials in animals is broader compared to humans, which can influence the increase in microbial resistance. This study was a systematic review which determined the prevalence of resistant Enterococcus faecium in commercial cattle. Eighteen studies were included, mainly carried out in European countries (n= 9) and in the production (n= 11) and retail (n= 7) environments. The main material used in the detection of the microorganism was milk. The mean prevalence of resistant E. faecium in cattle was 4.3% (95% CI= 2.8–5.0%), but the prevalence in Asia was higher [25.4% (95% CI= 20.5-30.6%)]. There was a higher prevalence in samples from retail (13.7%; 95% CI= 11.5-16.1%) and collected mainly from equipment surfaces (12.5%; 95% CI= 5.5-26.1%) than in the others tested samples. Antibiotics frequently tested were vancomycin, tetracycline, ciprofloxacin, and erythromycin, with resistance percentages of 50%, 59%, 79%, and 94%, respectively. These results reinforce the need to plan interventions to reduce antimicrobials in food-producing animals.